The Problem of â€œWomenâ€™s Workâ€ and the Idea of Work Democratization for the Liberating Empowerment of Women - Izzati, Fathimah Fildzah (Yayasan Jurnal Perempuan, 2019)
Women never make choices about their work democratically. In patriarchal society, â€œwomenâ€™s workâ€ is constructed as work that is in the area of social reproduction and is â€œnaturalâ€ for women. Consequently, women are increasingly in a vulnerable position in the labor market. In addition, women also face obstacles to being actively involved in various democratic spaces such as unions and womenâ€™s movements, and wider social movements because they bear a double workload that is life-consuming. However, various womenâ€™s empowerment programs launched by a number of development institutions to overcome the problems faced by women turned out to be far from womenâ€™s interests. Empowerment, also known as â€œliberal empowermentâ€, actually depoliticized and atomized women. Feminist scholars also call for the importance of realizing â€œliberating empowermentâ€. Related to that, this paper sees that the process of democratization of work on womenâ€™s work is an effort that can be done to pave the way for womenâ€™s liberation.Â